The Canadian Glomerulonephritis Registry (CGNR) and Translational Research Initiative: Rationale and Clinical Research Protocol. (April 2022) - Hildebrand, Ainslie M.; Barua, Moumita; Barbour, Sean J.; Tennankore, Karthik K.; Cattran, Daniel C.; Takano, Tomoko; Lam, Ping; De Serres, Sacha A.; Samanta, Ratna; Hladunewich, Michelle A.; Fairhead, Todd; Poyah, Penelope; et al.
Background: Glomerulonephritis (GN) is a leading cause of kidney failure and accounts for 20% of incident cases of end-stage kidney disease (ESKD) in Canada annually. Reversal of kidney injury and prevention of progression to kidney failure is possible; however, limited knowledge of underlying disease mechanisms and lack of noninvasive biomarkers and therapeutic targets are major barriers to successful therapeutic intervention. Multicenter approaches that link longitudinal clinical and outcomes data with serial biologic specimen collection would help bridge this gap. Objective: To establish a national, patient-centered, multidimensional web-based clinical database and federated virtual biobank to conduct human-based molecular and clinical research in GN in Canada. Design: Multicenter, prospective observational registry, starting in 2019. Setting: Nine participating Canadian tertiary care centers. Patients: Adult patients with a histopathologic pattern of injury consistent with IgA nephropathy, focal and segmental glomerulosclerosis, minimal change disease, membranous nephropathy, C3 glomerulopathy, and membranoproliferative GN recruited within 24 months of biopsy. Measurements: Initial visits include detailed clinical, histopathological, and laboratory data collection, blood, urine, and tonsil swab biospecimen collection, and a self-administered quality of life questionnaire. Follow-up clinical and laboratory data collection, biospecimen collection, and questionnaires are obtained every 6 months thereafter. Methods: Patients receive care as defined by their physician, with study visits scheduled every 6 months. Patients are followed until death, dialysis, transplantation, or withdrawal from the study. Key outcomes include a composite of ESKD or a 40% decline in estimated glomerular filtration rate (eGFR) at 2 years, rate of kidney function decline, and remission of proteinuria. Clinical and molecular phenotypical data will be analyzed by GN subtype to identify disease predictors and discover therapeutic targets. Limitations: Given the relative rarity of individual glomerular diseases, one of the major challenges is patient recruitment. Initial registry studies may be underpowered to detect small differences in clinically meaningful outcomes such as ESKD or death due to small sample sizes and short duration of follow-up in the initial 2-year phase of the study. Conclusions: The Canadian Glomerulonephritis Registry (CGNR) supports national collaborative efforts to study glomerular disease patients and their outcomes. Trial registration: NCT03460054.